HOW TO MAINTAIN HIGH QUALITY CARDIOPULMONARY RESUSCITATION IN ADULTS : LITERATURE REVIEW - Sapuan Sapuan (UPT Penerbitan Universitas Jember)
Intra-Hospital Cardiac Arrest (IHCA) incidence isquite high and varies with an average of 3.8 to 13.1per 1000 patient. Most IHCA (60%) due to heartproblems such as pulseless electrical activity (PEA),asystole, and the combined ventricular fibrillationventriculartachycardia. While, the cause IHCA byhypoxia about 30% (Becker, Aufderheide, &Graham, 2015). The mortality rate are recordedvery high. America Heart Association (AHA) statedthat only 14% of adults and 27% of children whosurvive after experiencing IHCA (Morrison, 2013).Cardiopulmonary resuscitation (CPR) is one of themost important emergency actions in lifethreatiningconditions. The performance ofcardiopulmonary resuscitation has an importantposition in the chain of survival, but despite newtechniques and technology the survival rates fromcardiac arrest are still low and the incidence of inhospitalcardiac arrest is rarely reported in theliterature. Cardiopulmonary resuscitation is acomplex of emergency procedures, if thatperformed correctly, can provide the necessaryminimum of circulation until return of spontaneouscirculation (ROSC) to patients with sudden cardiacarrest (Stiell, et. al., 2012). The high incidence, lowrate of survival, and unpredictability of cardiacarrest makes it a grave public health issue and amedical emergency. The application of CPR plays acritical role in saving lives from cardiac arrest in thehospital, and chest compression is the first part toplays a key role in CPR. (Chen, et al, 2015). Highqualitychest compressions of sufficient depth andrate with full recoil of the chest betweencompressions and avoidance of interruptions arecrucial to patient survival. The efficiency of CPR indecreasing the death rate from avertable causes isa very important factor. However there arerelatively few data available on the efficiency ofcardiopulmonary resuscitation in hospitals, whichplay an essential role in the chain of survival.Despite the fact that the cardiopulmonaryresuscitation was introduced more than 50 yearsago, the survival rate is still relatively low and thereis no trend of improvement of the situationobserved, although the technologies havedeveloped rapidly (Neumar, et.al., 2015).The survival of patients with cardiac arrestdepends on the quality of CPR is given. The successof CPR can be seen from the results whether thepatient is awake and back to life with normalfunction or only slightly deformed, conscious andreturned with moderate disabilities, unconsciouswith severe disabilities, coma or vegetative state,brain death, or death from other causes(Lallestedt, 2011).Although resuscitation guidelines provide a logical,sequential algorithmic approach, they have mainlyemphasized technical tasks performed byindividual rescuers and have not addressed issuesof adapting to the complex nature of most actualresuscitations. Part of this complexity relates tothe fact that in a healthcare environmentresuscitations are usually performed by teams ofresponders, not by isolated rescuers (Bhanji, et.al.,2011). Therefore, high quality CPR must be appliedin each treatment in cardiac arrest by usingmethods and best performance to maintain thequality of life of patients.